(untitled) (Argos, 2024)
This paper presents a critical and hermeneutic analysis of Epicurus’ thesis about the origin of language as stated in his single brief testimony, consisting of two paragraphs from his Letter to Herodotus. This analysis reveals the markedly problematic character of the theorisation, which does not seem to contain a proper explanation on the origin of language. By means of a theoretical reconstruction of the process underlying Epicurus’ statement and on the basis of a comparison with the classical perspective of language (Platonic and Aristotelian), the main gaps in the thesis under analysis are pointed out.